Foreign trade and sustainable business practices - New evidence from Ghana - Charles Godfred Ackah; Holger Görg; Aoife Hanley; Cecília Hornok (Kiel Centre for Globalization (KCG), 2020)
Foreign trade and sustainability is high on the political agenda. German and international policy-makers undertake increasing efforts to use trade policy more effectively for sustainable development purposes. A growing toolbox is meant to facilitate these policy aims, including sustainability chapters in trade agreements, sustainable value chains and sustainability standards. Meanwhile, scientific evidence on how trading activities impact on firms' sustainable behaviour is limited. This question is addressed by researchers from the Kiel Institute for the World Economy and the University of Ghana in a recent study 'Foreign Trade and Sustainable Development in Ghana'. The study provides new empirical evidence on the link between business sustainability and firms' engagement in international trade, using a survey database for more than 400 Ghanaian firms spanning 2013-2015, plus four case studies based on interviews. This unique information source provides a previously untapped wealth of information on various aspects of business sustainability in a Sub-Saharan African country. The key findings of the study are summarized in this policy paper.
Keywords: 330; Africa; Ghana; foreign trade; sustainability